2008
DOI: 10.1111/j.1574-6941.2008.00499.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the nodularin synthetase genes in the Baltic Sea bloom-former cyanobacterium Nodularia spumigena strain AV1

Abstract: Cyanobacterial blooms in the Baltic Sea are a common phenomenon and are formed by the heterocystous, filamentous species Nodularia spumigena. The toxicity of these blooms is attributed to the hepatotoxin nodularin, produced by N. spumigena. Little is known regarding the regulatory mechanisms or environmental signaling that control nodularin production. Here we report the characterization of the transcriptional expression pattern of the nodularin synthetase gene cluster (nda) during phosphate depletion, and nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 37 publications
0
28
1
Order By: Relevance
“…The latter is supported by findings of Møgelhøj et al (2006) and Suikkanen et al (2006), who found no evidence for pure nodularin having allelopathic properties against Rhodomonas sp. Also, Jonasson et al (2008) suggested that nodularin is not a secondary metabolite, but an important primary intracellular nitrogen compound, because N. spumigena cells continuously express the nodularin synthetase genes and maintain a threshold level of nodularin in cells. This view about a physiological role of nodularin is supported by the positive relationship between exponential growth and nodularin cellular concentration in monocultures (Lehtimäki et al 1994).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter is supported by findings of Møgelhøj et al (2006) and Suikkanen et al (2006), who found no evidence for pure nodularin having allelopathic properties against Rhodomonas sp. Also, Jonasson et al (2008) suggested that nodularin is not a secondary metabolite, but an important primary intracellular nitrogen compound, because N. spumigena cells continuously express the nodularin synthetase genes and maintain a threshold level of nodularin in cells. This view about a physiological role of nodularin is supported by the positive relationship between exponential growth and nodularin cellular concentration in monocultures (Lehtimäki et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, copepods could have caused changes in nutrient conditions, potentially affecting nodularin production. Indeed, Jonasson et al (2008) found that the expression of nodularin synthetase genes decreases in the presence of ammonium. In our experiments, all nutrients were supplied at saturating levels at the start of each experiment, which is indicated by the constant growth rate in Tetraselmis suecica (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in Lake Agawam, toxic Anabaena was not detected. Previously the qPCR assay for the ndaF gene of Nodularia spumigena was used to study gene expression changes in response to nutrient levels in Baltic Sea samples (15). The chip assay, although not quantitative, can be used to simultaneously identify all the main microcystin and nodularin producers present, expediting the analysis of large sample sets.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies are available in which RNA was used for identification of microcystin producers in natural environments by PCR (8,11). Expression of biosynthesis genes of nodularin, a toxin resembling microcystin but produced solely by Nodularia spumigena, was detected by qPCR in Baltic Sea samples (15).…”
mentioning
confidence: 99%